Peningkatan Mutu dan Cara Produksi pada Industri Minuman Jahe Merah Instan di Desa Benteng, Ciampea, Bogor - Sutrisno Koswara; Astrid Diniari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
Red ginger (Zingiber officinale var. Rubrum) have been processed into several foods and beverages, such as instant beverage, ginger candy, ginger pickle, ginger coffee, etc. This study aimed to study the optimum formulation of red ginger instant drinks and the most effective comparison of solubility with water, implement food security at household industry, and examine the financial aspects in the industrial of red ginger instant drinks at Benteng Village, Ciampea, Bogor. On determining the best formula, tested on 3 formula: formula with ratio sugar and red ginger 1:2 (A), 1:1 (B), and 1:3 (C). The yield of each formula was different which 66.33% ( formula A), 42.67% (formula B), and 69.33% (formula C). The best formula chosen is C because the materials used for the manufacture of the most economical and fast rehydration time. After following several processed of certification, the household industry of Jahe Gunung Leutik got the PIRT number as follow 61232010110099. Feasibility analysis also showed that the domestic industry was declared worthy of financial side. Based on the result of cost calculation of production of instant drink obtained that Rp 4.735.71. The result of instant drinks red ginger feasibility are NPV = Rp 917.725.03, gross B/C = 1.8244, net B/C = 3.8910, and IRR= 53%.